ANALISIS KOMPARATIF IMPLEMENTASI ENERGY STORAGE SYSTEM BATERAI LITHIUM-ION (LI-ION) DAN PUMPED HYDRO ENERGY STORAGE (PHES) - Tateng Sukendar; Wijayanto, Erwin (Universitas Dirgantara Marsekal Suryadarma, 2025)
As the demand for clean and sustainable energy continues to rise, energy storage systems (ESS) have become a crucial element in supporting the stability and efficiency of power systems, particularly in the integration of renewable energy sources. This study aims to conduct a comparative analysis of various energy storage technologies, including lithium-ion batteries, flow batteries, supercapacitors, and mechanical energy storage systems (pumped hydro and flywheels), in terms of efficiency, capacity, cost, reliability, and application potential. The research methodology involves literature review, technical and economic analysis, as well as evaluation of implementation cases in several countries. The results of the analysis indicate that no single technology is universally superior; instead, the selection of storage technology should be tailored to system requirements, energy source characteristics, and geographical and economic conditions. This study also discusses the potential implementation in Indonesia and the challenges faced, such as regulations, infrastructure, and investment costs. Policy recommendations and implementation strategies are presented as part of efforts to promote the adoption of energy storage technologies in the transition toward a sustainable energy system. Keywords: energy storage technology, batteries, supercapacitors, efficiency, renewable energy, Indonesia.